2021
DOI: 10.3389/fmars.2021.658417
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Natural and Anthropogenic Stressors on Fucalean Brown Seaweeds Across Different Spatial Scales in the Mediterranean Sea

Abstract: Algal habitat-forming forests composed of fucalean brown seaweeds (Cystoseira, Ericaria, and Gongolaria) have severely declined along the Mediterranean coasts, endangering the maintenance of essential ecosystem services. Numerous factors determine the loss of these assemblages and operate at different spatial scales, which must be identified to plan conservation and restoration actions. To explore the critical stressors (natural and anthropogenic) that may cause habitat degradation, we investigated (a) the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…Differently from Bianchi et al (2018) we found that two other large brown seaweeds, Cystoseira compressa and Dictyopteris polypodioides, are still generally common on the island, although with distribution concentrated in certain habitats and certain parts of the shoreline (Table 1). These are two widespread Mediterranean phaeophytes that thrive in a wide range of environmental conditions and may also occur at sites moderately affected by anthropogenic disturbances (Mangialajo et al 2008;Mancuso et al 2018;Orfanidis et al 2021). We also confirm the presence of Gongolaria elegans in the rockpool on the SE shore, where this species was previously recorded by Mangialajo (2007).…”
Section: Discussionsupporting
confidence: 85%
“…Differently from Bianchi et al (2018) we found that two other large brown seaweeds, Cystoseira compressa and Dictyopteris polypodioides, are still generally common on the island, although with distribution concentrated in certain habitats and certain parts of the shoreline (Table 1). These are two widespread Mediterranean phaeophytes that thrive in a wide range of environmental conditions and may also occur at sites moderately affected by anthropogenic disturbances (Mangialajo et al 2008;Mancuso et al 2018;Orfanidis et al 2021). We also confirm the presence of Gongolaria elegans in the rockpool on the SE shore, where this species was previously recorded by Mangialajo (2007).…”
Section: Discussionsupporting
confidence: 85%
“…As a result of multiple anthropogenic impacts (e.g., coastal urbanisation, eutrophication, sediment loading and overgrazing), Cystoseira stands have gradually disappeared in many Mediterranean coastal areas, often being replaced by filamentous or ephemeral taxa (e.g., Mangialajo et al, 2008;Falace et al, 2010;Vergeś et al, 2014;Thibaut et al, 2015;Rindi et al, 2017;Rindi et al, 2018;Catra et al, 2019;Mariani et al, 2019;Bernal-Ibañez et al, 2021;Orlando-Bonaca et al, 2021a;Orfanidis et al, 2021). In addition, human changes in the marine environment also affect connectivity, leading to habitat fragmentation and loss, and genetic disjunction even at small spatial scales (Alberto et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Gongolaria barbata (Stackhouse) Kuntze [formerly known as Cystoseira barbata (Stackhouse) C. Agardh; Molinari-Novoa & Guiry, 2020], an engineering species growing in shallow and sheltered environments, has seen its already limited distribution in the Mediterranean reduced over time (Orfanidis et al, 2021). This macroalga is currently considered as threatened by the Barcelona Convention (Annex II; UNEP/MAP, 2013).…”
Section: Introductionmentioning
confidence: 99%